Development of a Gamification-Based Virtual Laboratory Media to Enhance Scientific Thinking Skills of Elementary School Students - Puspitasari, Puspa; Uswatun, Din Azwar; Sutisnawati, Astri (Journal of Educational Sciences, 2026)
Science learning in elementary schools still faces problems, especially in practical activities that result in low scientific thinking skills. This study aims to develop gamification-based virtual laboratory media as a solution to improve scientific thinking skills in science learning in elementary schools. This study applied a Research and Development (R&D) approach by adapting the Borg & Gall model to evaluate the feasibility and effectiveness of the developed product. The media was designed in a website format that integrated images, materials, visualizations, instructional videos, virtual practical activities, and interactive quizzes. Expert validation results showed that the developed media was feasible for use with a rating in the excellent category. In addition, the effectiveness test results showed an increase in scientific thinking skills based on pretest and posttest scores after using the gamification-based virtual laboratory media. Thus, this study shows that gamification-based virtual laboratory media is feasible to use and effective in improving scientific thinking skills in science learning in elementary schools.